PATIENT PERSPECTIVE ON ADHERENCE TO ORGANIZATIONAL PRINCIPLES IN DENTAL PRACTICE - Rapis Anca; Nicolaiciuc Ovidiu; Rudnic Ioana; Feier Ramona; Nicolau Andrei; Panaite Tinela; Nemțoi Ana; Romanec Cristian; Armencia Adina; Balcoș Carina (Romanian Dental Association for Education, 2023)
The clinical activity in dental offices carries a heightened risk of pathogen transmission through direct contact with contaminated products, indirectly via instruments and equipment, and through cross-infection. This study aimed to evaluate patient perceptions of adherence to organizational principles in private dental practices. Material and Methods: To gauge public attitude and knowledge about the safety of medical procedures and infection control in dental offices, a questionnaire study was conducted with 75 patients undergoing dental treatments in two private clinics in Iași, aged between 20 and 75 years. Results: Patients believe they can contract diseases such as viral hepatitis B (76.3%), HIV infection (100%), viral hepatitis C (82.5%), viral hepatitis A (12.5%), influenza (96.5%), tuberculosis (23.7%), and chickenpox, smallpox, rubella (0.5 - 2.8%) during dental treatments. 96% of patients are unwilling to visit a dental clinic that previously treated an HIV-infected patient. 27% discussed with their dentist the risk of contracting diseases from dental treatments. 65.5% believe that a dentist infected with HIV can provide dental treatments if protective equipment (mask, gloves, glasses) is used. 100% agree that gloves and masks are essential for the dentist during treatment. Conclusions: Patients have a good understanding of the causes of infection transmission in dental clinics and how medical activities should be organized to reduce this risk. Continuous medical education and the implementation of specific programs should aim to increase compliance with infection control measures among both dentists and patients.